Determination of the Optimum Combination of Parameters of Specialized Blades for the Shantui SD 32 Bulldozer When Moving Low-Density Materials - Tavbay Khankelov; Maloxat Abdukadirova; Otabek Ochildiev; Zebo Alimova; Gulxayo Niyazova; Anvar Kadirov (Communications, 2025)
Recommendations are given on combinations of parameters of box-shaped and "dump" types of dumps for the SHANTUI SD 32 bulldozer, which provide the highest technical characteristics of the bulldozer when moving low-density materials. The optimal dimensions of a box blade for equipping the SHANTUI SD32 bulldozer are a grasp width of up to 3730 mm, radius of curvature of up to 1700 mm, width of the cutting edge of up to 460 mm, canopy width of up to 140 mm, flap length of up to 860 mm. The optimal dimensions of a "landfill" blade for equipping the SHANTUI SD32 bulldozer are a grasp width of up to 3900 mm, radius of curvature of up to 460 mm, width of the cutting edge of up to 124 mm, canopy width of up to 610 mm.